EVALUATION OF THE LEVEL OF ECONOMIC EFFICIENCY OF IRRIGATED TOMATO PRODUCTION UNDER KANO RIVER IRRIGATION PROJECT, NIGERIA - Ahmed, Bashir Sa’ad; Abdulsalam, Zakari; Maiyaki, Abdullahi Damisa (FUDMA JOURNAL OF SCIENCES, 2022)
The broad objective of the study was to evaluate the Level of Economic Efficiency of Irrigated Tomato Production under Kano River Irrigation Project, Nigeria. A multi-stage sampling techniques was used to select 213 irrigated tomato farmers. Primary data was used and were collected using well-structured questionnaire. Data collected were analysed using descriptive statistics such as frequency, percentages and data. The result of the analysis revealed that the average economic efficiency of the irrigated tomato farms was 67%. This indicates that irrigated tomato farms were economically inefficient. It can be concluded that all the three categories of irrigated tomato farms were economically inefficient with large irrigated tomato farms having the highest economic efficiency of 67% in the study area. It is therefore recommended that agricultural extension workers should be provided to disseminate research finding and educate irrigated tomato farmers on ways of improving their economic efficacy